Rekonstruksi Penetapan Anak Biologis dari Hasil Perkawinan Tidak Sah Dalam Putusan Pengadilan Agama - Muhammad Idris Nasution; Mhd. Syahnan; Fauziah Lubis (Jurnal Hukum IUS QUIA IUSTUM, 2024)
The legal norm contained within Article 42 of the Marriage Law rigidly stipulates that the legal validity of a child depends on the legality of the marriage of their biological parents. The provisions of this norm have raised legal problems for children from illegitimate marriages, especially concerning their civil rights. Departing from the Constitutional Court Decision Number 46/PUU-VIII/2010 which gave rise to a controversial discourse by giving illegitimate children the right to a civil relationship with their father, the Religious Court formulated a new norm for the status of children as biological children to accommodate the protection of children's rights, but there remain legal issues in determining such status and in practice, it remains unable to accommodate children's civil rights. This study aims to explore the considerations of the Religious Court's decision in determining biological children and its legal consequences for the enforcement of children's civil rights, and then offer a legal reconstruction of the determination of biological children. This  is a normative legal research with a statutory approach, a case approach, and a conceptual approach. Data analysis is qualitative with seven thematic steps. The results of this study indicate that in considering the decision of the Religious Court, the judge considered the marriage carried out by the parties invalid because the marriage witnesses and marriage guardians were invalid. In the judge's view, an illegitimate marriage is adultery, so that the child born from it is a child of adultery, so he cannot be related to his father, but they can still obtain other limited civil rights. This study concludes that there is a fatal misconception in placing children from illegitimate marriages as children of adultery or biological children. Determination of the child's status as a biological child in the decision of the Religious Court is a legal formulation that is contrary to the norms of the Marriage Law, Islamic Law, and fiqh. The legal construction in determining the status of a biological child is not oriented towards substantial justice for children, contrary to the principle of liability based on fault, retributive justice, and the principle of nemo commodum capere potest de injuria sua propria. However, this legal construction is based on the norm of Article 42 of the Marriage Law, for that it must be reconstructed. The substantial justice approach requires that children born in or as a result of an illegitimate marriage must continue to be treated as legitimate children with all the legal consequences.Keywords: Biological Children, Illegal Marriage, Religious Court Decisions, Legal Reconstruction AbstrakNorma Pasal 42 Undang-Undang Perkawinan menetapkan secara rigid hukum keabsahan anak bergantung pada keabsahan pernikahan orang tua biologisnya. Ketentuan norma ini telah menimbulkan problematika hukum terhadap anak hasil perkawinan yang tidak sah, terutama menyangkut hak-hak perdatanya. Berangkat dari Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 yang melahirkan wacana kontroversial dengan memberikan anak luar kawin hak berupa hubungan perdata dengan ayahnya, Peradilan Agama memformulasi norma baru status anak berupa anak biologis untuk mengakomodasi perlindungan hak anak, tetapi terdapat problem hukum dalam penetapan status ini dan dalam praktiknya tidak benar-benar dapat mengakomodasi hak perdata anak.  Penelitian ini hendak menggali pertimbangan putusan Pengadilan Agama dalam penetapan anak biologis dan akibat hukumnya terhadap penegakan hak-hak perdata anak, dan selanjutnya menawarkan rekonstruksi hukum terhadap penetapan anak biologis. Penelitian ini bersifat hukum normatif dengan pendekatan perundang-undangan, pendekatan kasus, dan pendekatan konseptual. Analisis data bersifat kualitatif dengan tujuh langkah tematik. Hasil penelitian ini menunjukkan bahwa dalam pertimbangan putusan Pengadilan Agama, hakim menilai pernikahan yang dilakukan oleh para pihak tidak sah karena tidak sahnya saksi nikah dan wali nikah. Dalam pandangan hakim, pernikahan yang tidak sah itu adalah zina, sehingga anak yang dilahirkan darinya adalah anak zina, maka ia tidak dapat dinasabkan kepada ayahnya, tetapi ia tetap dapat memperoleh hak-hak perdata lainnya secara terbatas. Penelitian ini menyimpulkan bahwa terdapat salah kaprah yang fatal dengan mendudukkan anak hasil perkawinan tidak sah sebagai anak zina atau anak biologis. Penetapan status anak sebagai anak biologis dalam putusan Pengadilan Agama merupakan formulasi hukum yang bertentangan dengan norma Undang-Undang Perkawinan, KHI, dan fikih. Konstruksi hukum dalam penetapan status anak biologis tersebut tidak berorientasi pada keadilan substansial bagi anak, bertentangan dengan prinsip liability based on fault, keadilan retributif, dan asas nemo commodum capere potest de injuria sua propria. Namun, kontruksi hukum ini berpangkal dari norma Pasal 42 Undang-Undang Perkawinan, untuk itu harus dilakukan rekonstruksi terhadapnya. Pendekatan keadilan substansial menghendaki anak yang dilahirkan dalam atau sebagai akibat perkawinan yang tidak sah harus tetap didudukkan sebagai anak yang sah dengan segala akibat hukumnyaKata Kunci: Anak Biologis, Perkawinan Tidak Sah, Putusan Pengadilan Agama, Rekonstruksi Hukum